Pendekatan Model Wasp Pada Pengendalian Pencemaran Sungai Dengan Parameter Uji Cod - Randhi Saily; Manyuk Fauzi; Imam Suprayogi (Universitas Trisakti, 2019)
The rapid development requires enormous natural resources. So it appears that in development there is an overuse of natural resources, which results in disruption of the water system balance. Various impacts will occur as a result of unbalanced use of natural resources, the use of unbalanced natural resources around the Siak river area, causing an increase in pollution entering the river. Regulation of the Minister of PUPR Number 4 of 2015 concerning Criteria and Designation of River Areas, Siak River is one of the major rivers that receive national attention and is also included in the national strategic river category. Control of river pollution is done by analyzing the WASP modeling and the existing condition of the Siak river, the effect of the levels on the parameters of the mainstay discharge and the mainstay discharge and the percentage of pollution load reduction carried out to meet the class II quality standards. The results showed that theoverall condition of the Siak river was polluted. The average excess capacity of the COD pollution load at the time of the depandable discharge is -454,516 kg/day. Then at the time of the depandable discharge isvalued at -181,087 kg/day. The control effort taken is to reduce the COD contamination load so that the capacity of the pollution load is +177,742 kg/day when the depandable discharge is maximum and +72,536kg/day when the depandable discharge is minimum. Percentage reduction of COD contamination load at the minimum and maximum depandable discharge to meet the class II quality standard of 50%.